STUDI LITERATUR PENGARUH PEMBERIAN EKSTRAK DAUN BAYAM MERAH (Amaranthus tricolor L.) TERHADAP KADAR SGOT DAN SGPT PADA TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR WISTAR YANG DIBERI DIET TINGGI LEMAK - Rusmini, Hetti; Ulfa, Ade Maria; Fitriani, Dita; Rifatunnissa, Lulu’ (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Background : The prevalence of hyperlipidemia in Indonesia is increasing from year to year, in 2008 it was recorded at 35.1%. Then in 2013 it increased to 35.9%(WHO, 2013). Increased hyperlipidemia triggers Non-Alcoholic Fatty Liver Disease (NAFLD)(Ghanaei et al., 2019). NAFLD conditions cause liver cell damage, causing increased levels of liver enzymes such as SGOT and SGPT (Prahastuti et al., 2020). According to Pradana et al. (2017) it is said that red spinach leaf extract has antioxidant activity that is able to inhibit the incision of the oxidation chain reaction because it contains flavonoid compounds, quercetin, tannins, and saponins which have the potential as a preventive therapy for fatty liver. Objective: To determine the effect of red spinach (Amaranthus tricolor L.) leaf extract on SGOT and SGPT levels in white rats (Rattus norvegicus) fed a high-fat diet. Research Methods: The research method uses a literature study. The database in the literature study was obtained from Google Scholar, PubMed and NCBI which was taken by Population, Intervention, Comparation, Output, Study, and Time (PICOST) from 5,166 journals and finally 8 journals were obtained. Results: Literature from 8 journals is known to have 8 that discuss red spinach leaf extract. Conclusion: From the literature obtained, there was an effect of giving red spinach leaf extract (Amaranthus tricolor L.) on the levels of SGOT and SGPT given a high-fat diet. The dose is 200mg/kgBB and 400mg/kgBB with a duration of administration of 7 to 29 days. Keyword : High fat diet, Red Spinach Extract, Hyperlipidemia, NAFLD, SGOT, SGPT, White Rat